Comparing Mouse and Human Tissue-Resident γδ T Cells - Qu, Guanyu; Wang, Shengli; Zhou, Zhenlong; Jiang, Dawei; Liao, Aihua; Luo, Jing (Frontiers in Immunology, 2022)
Circulating immune cell compartments have been extensively studied for decades, but limited access to peripheral tissue and cell yield have hampered our understanding of tissue-based immunity, especially in γδ T cells. γδ T cells are a unique subset of T cells that are rare in secondary lymphoid organs, but enriched in many peripheral tissues including the skin, uterus, and other epithelial tissues. In addition to immune surveillance activities, recent reports have revealed exciting new roles for γδ T cells in homeostatic tissue physiology in mice and humans. It is therefore important to investigate to what extent the developmental rules described using mouse models transfer to human γδ T cells. Besides, it will be necessary to understand the differences in the development and biogenesis of human and mouse γδ T cells; to understand how γδ T cells are maintained in physiological and pathological circumstances within different tissues, as well as characterize the progenitors of different tissue-resident γδ T cells. Here, we summarize current knowledge of the γδ T phenotype in various tissues in mice and humans, describing the similarities and differences of tissue-resident γδ T cells in mice and humans.